Recent Progress in Light-Driven Molecular Shuttles - Yao, Bin; Sun, Hongfei; Yang, Lin; Wang, Song; Liu, Xingyan (Frontiers in Chemistry, 2022)
Molecular shuttles are typical molecular machines which could be applied in various fields. The motion modes of wheel components in rotaxanes could be strategically modulated by external stimuli, such as pH, ions, solvent, light, and so on. Light is particularly attractive because it is harmless and can be operated in a remote mode and usually no byproducts are formed. Over the past decade, a large number of examples of light-driven molecular shuttles are emerging. Accordingly, this review summarizes the recent research progress of light-driven molecular shuttles. Firstly, the light-driven mechanisms of molecular motions with different functional groups are discussed in detail, which show how to drive photoresponsive or non-photoresponsive molecular shuttles. Subsequently, the practical applications of molecular shuttles in different fields, such as optical information storage, catalysis for organic reactions, drug delivery, and so on, are demonstrated. Finally, the future development of light-driven molecular shuttle is briefly prospected.